Implementasi Pasal 9 Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan Melalui Baitul Arqamdi Universitas Muhammadiyah Sukabumi - Asti Sri Mulyanti; Prahasti Suyaman, Prahasti Suyaman; Leonita Siwiyanti, Leonita Siwiyanti (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2024)
Human Resources has an important role in creating organizational success which has the function of planning, organizing, directing and supervising, procurement, development, compensation, integration, maintenance and termination of employment with the intention of achieving organizational goals in an integrated manner able to achieve success in achieving the vision and mission of the organization. The implementation of Law Number 13 of 2013 concerning Manpower is an important target of this study, to test the extent of the effectiveness of the policy. The method used in the study is normative juridical which focuses on the analysis of legislation. This approach aims to analyze the extent of the meaning and implications of the norms of laws and regulations that become a legal policy. So that with this approach it is possible to identify the relationship between these norms and the existing reality. Universitas Muhammadiyah Sukabumi through the Baitul Arqam program which is carried out regularly can implement the regulation to provide training and development for employees in improving performance towards work ethic